Current indications and patient selection for transoral robotic surgery in head and neck cancer: a brief review - Niewinski, Patryk; Golusiński, Wojciech (Contemporary Oncology/Współczesna Onkologia, 2022)
Transoral robotic surgery (TORS) continues to gain momentum in minimally invasive surgery. Not only is TORS potentially curative in many cases, but it also addresses the growing emphasis on functional outcomes and quality of life. The main anatomical areas in which TORS is used are the oropharynx and larynx; however, it is becoming increasingly common in thyroid surgery and neck dissections. With growing popularity, the number of indications for TORS in oropharyngeal and laryngeal cancer also increases. However, not all patients are good candidates for this technique, and thus patient selection is essential, with careful assessment of patient-related factors (e.g. comorbidities and endoscopic access) and disease-related variables, such as tumour location, disease staging, and the involvement of surrounding anatomical structures. The aim of the present article is to briefly review the current and emerging indications for TORS in head and neck cancer and the main factors related to patient selection.